Pengaruh Kompetensi Manajerial Kepala Madrasah Dan Motivasi Kerja Terhadap Profesionalisme Guru - Suyono Triwibowo; Tadjoer Ridjal; Adibah Jauhari; Abdul Rouf (FAI- Undar, 2019)
Management is very important in all our of life. Management of education in Indonesia has not appeared as desired professional ability, the management problem education is one of the fundamental problems that caused the crisis in Indonesia. The purpose of this research is to analysis influence of the Principal managerial competence and work motivation on teachers profesionalism teachers in Islamic Yunior School of Caruban Madiun. The population and sample in this research is all the teachers in Islamic Yunior State School of Caruban Madiun there are 38 teachers, because the population less than 100 in its account, the sample is taken from the population. Design of this research is quantitative research because testing relationship with three variable there is Principal Managerial Competence, Work Motivation and Teachers Profesionalism. Collecting data methods using questionnaire which is given to all the teachers in Islamic Yunior School of Caruban as the respondents that analyzed using pearson influence and proceed with 17th version of SPSS software. The results of this study indicate that: (1) there is a positive significant (p = 0,00) the influence of Principal managerial competence on Profesionalism teachers in Islamic Yunior School of Caruban Madiun(2) positive significant (p = 0,00) influence Work motivation on Teachers Profesionalism in Islamic Yunior State School of Caruban Madiun (3) positive significant (p = 0,000) simultanly influence of principal managerial competence and Work motivation on Profesionalism teachers in Islamic Yunior State School of Caruban Madiun through Y = 7.815 + 0.556X1 + 0.308X2